NILAI GIZI BERAS LIMA VARITAS PADI UNGGUL - Hong, Lie Goan; Nio, Oey Kam; Prawiranegara, Dradjat D. (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
Nilai gizi beras lima varitas padi unggul. (The nutritional value of rice of five high-yielding varieties). Presented at the First Asian Congress of Nutrition, Hyderabad, January 28 - February 2, 1971. The protein contents of IRRI rice varieties were: 7% in PB 5 (IRRI 5), 6.4% in PB 8 (IRRI 8) and 9% in C4-63. The Indonesian high-yielding rice varieties had protein contents of 6% in Shinta, and 7.3% in Dewi Ratih, compared to 6% in brown rice. The PER values of PB 5 and PB 8 were 2.3 and 2.5 while that of Shinta and brown rice were 2.2 and 2.1. The PER value of skimmed milk was 2.9. The NPU-op values of those four rice varieties ranged from 52 to 54, but was only 40 for C4-63. Fortification with L-lysine monohydrochloride increased the NPU. Varitas-varitas padi PB 5 dan PB 8 lebih disukai orang karena lebih enak rasanya, terutama jenis Shinta dan C4-63. Menjadi pertanyaan apakah jenis-jenis ini mempunyai kualitas protein yang lebih baik, disamping daya hasil tinggi dan ciri-ciri lain. Penelitian ini ditujukan untuk mencari nilai gizi beras kelima varitas padi.